Scientific and clinical studies in laryngology and phoniatrics at the Department of ear, nose and throat diseases I.M. Sechenov First Moscow State Medical University: the continuity of generations - V. M. Svistushkin; S. V. Starostina; E. B. Rakunova; L. V. Eremeeva; E. Ye. Avetisyan (Сеченовский вестник)
This article describes the historical background and contemporary issues of laryngology and phoniatrics in I.M. Sechenov First Moscow State Medical University. As well as the research into organic and functional pathology of larynx done at the Department.